Business incubator models in the US and Korea - Yun, Boyun (KDI School, 2000)
Business incubators in the New Economy are seen as entities that help to create successful new ventures by providing speed-to-market, synergy, network, talent, and capital. This study examines the business models of various business incubators and analyzes the case of three early movers: Idealab, CMGI, and ICG. These incubator business models are classified by organization type and operating type. Even though each business model has different value focus, this study analyzes the overall value proposition and risks of business incubators and identifies some of the key factors for success. This study also examines the current status of business incubators in Korea and offers some suggestions for improvement
Thesis(Master) --KDI School:Master of Business Administration,2000